The Social Construction of Paternity in Men of Rural Contexts of Morelos, Mexico - Rodríguez Abad, Angélica (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2019)
This article analyzes the meanings and experiences of the paternity of the men in three counties ofMorelos State, based on the ruptures and permanence of the paternity learned from their parents, ofthe transitions when they are parents, the agreements and disagreements with their partners, and thesearch for a participatory, active, collaborative and equitable paternity, which arise from reflectionson the difficulties, obstacles and criticisms of the social context in which they live.